Produção de carotenoides por Sporobolomyces ruberrimus em fermentação contínua a partir de melaço de canadeaçúcar - Jacojaco, Fernando Kenji (2012)
Carotenoids are natural pigments with antioxidant function, commercially produced by chemical synthesis, extraction from vegetable sources or microbial synthesis. Their applications include food additive, feeding supplement and pharmaceutical products components. The present work describes carotenoids (γ−carotene, β−carotene, torulene and torularhodin) production and growth kinetics of Sporobolomyces ruberrimus in a chemostat fermenter, using sugarcane molasses as substrate. The optimized culture conditions (temperature, pH, aeration, stirring and volume), previously defined by the work group, were constant at different dilution rates. Culture media and fermented broth were characterized for biomass concentration, measured by optical density; total carbohydrates, measured by DNS method; and total carotenoids, measured by spectrophotometry, after cell disruption by mechanical method and extraction with organic solvents. Data were used to determine the values of Monod saturation constant KS, maximum growth rate µmax, true cellular growth yield YG, maintenance coefficient mS, and the Luedeking−Piret α and β coefficients. The results were 46.57 g.L−1 , 0.19 h−1 , 0.25 g.g−1 , 0.016 h−1 , 0.25 mg.g−1 and 0.00 mg.g−1 . Obtained µmax is similar to the results previously described in literature. Luedeking-Piret coefficients indicate that torularhodin is a growthassociated metabolite. Also this red yeast has particular characteristics. It has a high KS value. This indicates that µmax can be reached only at high sugarcane molasses concentration.